Kesadaran Mahasiswa sebagai Warga Negara dalam Memahami Hak dan Tanggungjawab Sosial terhadap Penggunaan Bahan Kimia Berbahaya pada Rokok - Dita Aulianti; Sri Yunita; Dinastini Daeli; Fathin Nadira; Khayla Akmal Panjaitan; Serlina Wati Azhari (International Forum of Researchers and Lecturers, 2024)
This research aims to analyze the awareness of Medan State University and Medan Area University (UMA) students as citizens in understanding social rights and responsibilities regarding the use of dangerous chemicals in cigarettes. The background to this research is based on the increasing consumption of cigarettes among students and its impact on health and the environment. The method used in this research is a qualitative approach with data collection techniques through interviews and observation. Interviews were conducted with students from various departments at both universities to explore their knowledge and attitudes regarding chemicals in cigarettes. Apart from that, observations were carried out in the campus environment to see cigarette consumption behavior among students. The research results show that students' awareness of their rights to obtain accurate information about the dangers of smoking and their social responsibility to educate their friends is still low. Therefore, more effective educational programs are needed to increase students' understanding of this issue and encourage proactive action in protecting themselves and the environment from the negative impacts of smoking.